1988
DOI: 10.1246/cl.1988.323
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectral Change of Crown Ethers and Related Polyethylene Glycol Dialkyl Ethers Due to Accommodation of Water

Abstract: Raman spectra of crown ethers and related polyethylene glycol dialkyl ethers in solutions were measured. The spectra showed remarkable characteristics, which are interpreted to be due to accommodation of water. Conformations of the crowns and the ethers accommodating water are similar to those in their complexes with cations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 5 publications
1
8
0
Order By: Relevance
“…43 Vibrational spectra of 18c6, free and its metal complexes, have been the focus of many studies. 46 The experimental structure of 18c6, in the free and in the metal-complex state, [47][48][49][50] has been reported. X-ray structural data of free 18c6 at room temperature 47 and at 100 K 48 indicated that free 18c6 in the solid phase has a C i structure.…”
Section: Introductionmentioning
confidence: 99%
“…43 Vibrational spectra of 18c6, free and its metal complexes, have been the focus of many studies. 46 The experimental structure of 18c6, in the free and in the metal-complex state, [47][48][49][50] has been reported. X-ray structural data of free 18c6 at room temperature 47 and at 100 K 48 indicated that free 18c6 in the solid phase has a C i structure.…”
Section: Introductionmentioning
confidence: 99%
“…The solvation, or more specifically the hydration, of simple crown ethers such as 12-crown-4 (12C4), 15-crown-5 (15C5), and 18-crown-6 (18C6) is of particular interest to understanding chemical recognition phenomena and the stability of host-guest complexes. The hydration has a strong effect on the conformation of the crown ring, which is best expressed for 18C6 aqueous solutions and has been well documented by a number of experimental techniques including Raman spectroscopy, [1][2][3][4][5][6] infrared spectroscopy, 7 X-ray diffraction, 8 quasielastic neutron scattering, 9 and ultrasonic velocity. 10,11 Computer simulations employing molecular mechanics, 12,13 molecular dynamics, [14][15][16][17] and Monte Carlo calculations 18,19 have successfully complemented the experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier calculations, such an approach allowed us to predict that the Du form of 18C6, of comparable intrinsic stability as the C, form, was significantly better hydrated and should, therefore, display the highest population in water,15 in agreement with subsequent theoretical studies16'33-34 and consistent with several experimental observations. [35][36][37] We consider conformers of 18C6 and 222 extracted from solid-state structures12 and solvated in acetonitrile. For 18C6, the simulation is run for 2 ns, which is the longest simulation reported so far to our knowledge for 18C6 in solution.…”
Section: Introductionmentioning
confidence: 99%